"Nothing but a False Sense of Security": Mapping and Critically Assessing Papal Support for a World Free from Nuclear Weapons. Issue 1 (2nd January 2019) - Hrynkow, Christopher
ABSTRACT: This article maps the papal peace witness' support for a world free from nuclear weapons. Although the last concentration of scholarly work in this area dates back to the early and mid-1980s, now is a cogent time to update that scholarship by revisiting and critically assessing papal teachings and diplomatic actions that move towards banning nuclear weapons on Earth. Contemporary events motivating this article include the need to bridge the gap evident in US and global policy on nuclear weapons. Particularly relevant here is the current "everything on the table"-themed posturing, oddly mixing war and peace themes, active in the Trump administration's policy of reinvigorating the USA's nuclear arsenal in the face of challenge by the likes of Kim Jong-un's nuclear ambitions for North Korea. Yet, at the same time a significant number of the members of the community of nations, including the Holy See, have signed the Treaty on the Prohibition of Nuclear Weapons. To undertake the task of critically mapping papal support for a world free from nuclear weapons that made it almost a given that the Holy See would sign and ratify that treaty, the present article examines the contributions of contemporary popes from Pius XII to Francis. It focuses on how these popes named and addressed what they often characterized as the moral evils manifest in nuclear weapons, when focusing their efforts to rid the world of these human-generated existential threats.